Development of an efficient route to CF3-substituted pyrrolopyrimidines through understanding the competition between Michael and aza-Henry reactions. Issue 5 (3rd December 2014) - Tkachuk, V. M.; Sukach, V. A.; Kovalchuk, K. V.; Vovk, M. V.; Nenajdenko, V. G.
Abstract : A simple control of temperature and time in the nitromethane addition to 4-trifluoromethylated pyrimidin-2-ones allowed regioselective synthesis of isomeric products. Abstract : The regioselective base-catalyzed addition of nitromethane to 2-oxo-4-trifluoromethyl-1, 2-dihydropyrimidine-5-carboxylates is reported. It was found that the Michael-like pathway is highly reversible and substantially dominating under conditions of kinetic control (0–5 °C, 10 h) whereas the aza-Henry reaction leads to thermodynamically stable adducts after 8–24 h exposure at room temperature. The adjacent nitro and alkoxycarbonyl groups were exploited to demonstrate the synthetic potential of the obtained products by converting to the isomeric trifluoromethylated pyrrolo[3, 4- d ]pyrimidine-2, 5-diones. With this aim an efficient protocol for selective reduction of nitro-derivatives to the corresponding 4- or 6-aminomethyl-2-oxo-4-trifluoromethyl-1, 2, 3, 4-tetrahydropyrimidine-5-carboxylates and their subsequent thermal cyclocondensations was applied.